2020
DOI: 10.3390/ijms21176079
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Atopic Dermatitis (AD): The Impact of Particulate Matter (PM10) on an AD Mouse-Model

Abstract: Air pollution reportedly contributes to the development and exacerbation of atopic dermatitis (AD). However, the exact mechanism underlying this remains unclear. To examine the relationship between air pollution and AD, a clinical, histological, and genetic analysis was performed on particulate matter (PM)-exposed mice. Five-week-old BALB/c mice were randomly divided into four groups (control group, ovalbumin (OVA) group, PM group, OVA + PM group; n = 6) and treated with OVA or PM10, alone or together. Cutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Air pollution may be related to the development and exacerbation of AD [ 30 , 31 , 32 , 33 ]. Woo et al [ 34 ] reported that PM 10 exposure induces and aggravates skin inflammation via the differential expression of genes controlling skin barrier integrity and immune response in ovalbumin (OVA)-treated mice. Li et al [ 35 ] proved that PM 2.5 promotes the expression of TSLP in PAM212 cells and may aggravate allergic responses through this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution may be related to the development and exacerbation of AD [ 30 , 31 , 32 , 33 ]. Woo et al [ 34 ] reported that PM 10 exposure induces and aggravates skin inflammation via the differential expression of genes controlling skin barrier integrity and immune response in ovalbumin (OVA)-treated mice. Li et al [ 35 ] proved that PM 2.5 promotes the expression of TSLP in PAM212 cells and may aggravate allergic responses through this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the mechanism behind this association has been limited. In a mouse model study, particulate matter exposure upregulated the expression of SPRR2D , S100A9 , STFA3 , CHIL1 , DBP , and IL1B , which are responsible for skin barrier integrity and immune response [ 18 ]. Another group revealed that skin inflammation induced by ambient particulate is attributable to oxidative stress or programmed cell death [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…PM 2.5 and PM 10 were associated with higher prevalence of eczema by some studies but protective factors in others [ 10 , 12 , 14 ], while some studies demonstrated that air pollution does not necessarily affect the development of eczema or AD [ 15 , 16 , 17 ]. Disruption of skin barrier integrity, immune-related responses, and alteration of gut microbiota have recently been proposed as the potential mechanisms of the association between air pollutants and atopic skin diseases [ 18 , 19 , 20 ]. The correlation between urticaria and air pollution has rarely been explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of air pollution has become prevalent worldwide, and interest in health problems caused by PM has also grown 1 2 . PM, a key constituent of air pollution, is known to increase the risk of cardiovascular, respiratory, nervous, and immune diseases 3 4 . Recently, the damaging effects of PM on the skin have been of great interest 5 6 .…”
Section: Introductionmentioning
confidence: 99%